Disrupted Self-Perception in People With Chronic Low Back Pain. Further Evaluation of the Fremantle Back Awareness Questionnaire - Wand, B.; Catley, M.; Rabey, M.; O'Sullivan, Peter; O'Connell, N.; Smith, A. (Churchill Livingstone, 2016)
Several lines of evidence suggest that body perception is altered in people with chronic back pain. Maladaptive perceptual awareness of the back might contribute to the pain experience as well as serve as a target for treatment. The Fremantle Back Awareness Questionnaire (FreBAQ) is a simple questionnaire recently developed to assess back-specific altered self-perception. The aims of this study were to present the outcomes of a comprehensive evaluation of the questionnaire's psychometric properties and explore the potential relationships between body perception, nociceptive sensitivity, distress, and beliefs about back pain and the contribution these factors might play in explaining pain and disability. Two hundred fifty-one people with chronic back pain completed the questionnaire as well as a battery of clinical tests. The Rasch model was used to explore the questionnaires' psychometric properties and correlation and multiple linear regression analyses were used to explore the relationship between altered body perception and clinical status. The FreBAQ appears unidimensional with no redundant items, has minimal ceiling and floor effects, acceptable internal consistency, was functional on the category rating scale, and was not biased by demographic or clinical variables. FreBAQ scores were correlated with sensitivity, distress, and beliefs and were uniquely associated with pain and disability.Perspective: Several lines of evidence suggest that body perception might be disturbed in people with chronic low back pain, possibly contributing to the condition and offering a potential target for treatment. The FreBAQ was developed as a quick and simple way of measuring back-specific body perception in people with chronic low back pain. The questionnaire appears to be a psychometrically sound way of assessing altered self-perception. The level of altered self-perception is positively correlated with pain intensity and disability as well as showing associations with psychological distress, pain catastrophization, fear avoidance beliefs, and lumbar pressure pain threshold. In this sample, it appears that altered self-perception might be a more important determinant of clinical severity than psychological distress, pain catastrophization, fear avoidance beliefs, or lumbar pressure pain threshold.